2019
DOI: 10.1596/1813-9450-9058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Salinity on Infant and Neonatal Mortality in Bangladesh

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…According to 37.32% of the respondent, pregnant women cannot drink the amount of water they need due to the lack of water availability, according to 33.87 % women experience bathing problems and 28.81% of them believe women face proper sanitation problems due to lack of fresh water. All these problems have relations to the health problems of pregnant women as child death and miscarriage is apparent among them (Hossain, 2020;Joseph et al, 2019). About 22.7% of the respondents highlight that salinity in water increases child mortality, have an impact on children's developments (according to 78.4% respondents) and some of them believe that miscarriage is triggered by the water crisis.…”
Section: Water Salinity and Gendered Health Impactsmentioning
confidence: 99%
“…According to 37.32% of the respondent, pregnant women cannot drink the amount of water they need due to the lack of water availability, according to 33.87 % women experience bathing problems and 28.81% of them believe women face proper sanitation problems due to lack of fresh water. All these problems have relations to the health problems of pregnant women as child death and miscarriage is apparent among them (Hossain, 2020;Joseph et al, 2019). About 22.7% of the respondents highlight that salinity in water increases child mortality, have an impact on children's developments (according to 78.4% respondents) and some of them believe that miscarriage is triggered by the water crisis.…”
Section: Water Salinity and Gendered Health Impactsmentioning
confidence: 99%
“…ity is comparable in magnitude to the estimated effects of traditionally cited variables (for example, maternal age and education, gender of household head, household wealth, toilet facilities, drinking water sources, and cooking fuels). Using nonparametric regression,Joseph et al (2019) reported higher infant mortality (death within 2 months, as well as 12 months, after birth) when drinking water salinity is high.…”
mentioning
confidence: 99%